URGENSITAS PELATIHAN DAN PENGEMBANGAN SUMBER DAYA MANUSIA - Reresi, Marsianus (LOGOS: JURNAL PENDIDIKAN KEAGAMAAN KATOLIK, 2016)
This article intends to provide some important features in relation to training and development as the operational manageral function of sources (MSDM) at any foundation or organisation. The central question which we endeavour to answer in this piece of writing is “What could be a strategic solution in relation to the enhancement of quality of human sources at a foundation or organisation?” Training and development of human sources should be acknowledged as a strategic and urgent solution, when the foundation or organisation is oriented on worthwile an qualifeid service.